THEOPHYLLINE ASCORBIC ACID COCRYSTALS BY SONOCRYSTALLIZATION METHOD: FORMULATION AND CHARACTERIZATION STUDIES - HARITA R DESAI; SAKSHI JAISWAL; ASHWINI KONDHARE (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of the current research work was to develop Theophylline Ascorbic acid cocrystals by sonocrystallization method. The approach is a coadministrative approach to provide drug:drug cocrystals in Chronic Obstructive Pulmonary Disorder. Methods:The cocrystals were formulated in 3 stoichiometric ratios of 1:1, 1:2 and 2:1 using Sonocrystallization induced evaporation method. Methanol was used as solvent. The cocrystals were evaluated for visual morphology, melting point, FTIR studies, saturation solubility in water and Simulated Lung fluid pH 7.4, in vitro drug release in Simulated Lung Fluid pH 7.4, Differential scanning calorimetry studies, X-Ray Diffraction studies, Scanning Electron Microscopy studies and Raman spectroscopy. Result:Cocrystals were successfully developed in all 3 stoichiometric ratios by sonocrystallization method. The cocrystal of Theophylline with Ascorbic acid in ratio of 1:1 was found to be most optimized with 10 fold increase in saturation solubility in water and 11.5 fold increase in solubility in simulated lung fluid pH 7.4 and two-fold increase in in vitro drug release in SLF pH 7.4. The cocrystal was found to show a lowered melting point as confirmed by DSC studies thus confirming formation of new crystalline phase. X Ray Diffraction studies. SEM and Raman spectroscopy studies were found to confirm the change in crystalline characteristics of the cocrystals by indicating formation of new crystalline phase. Conclusion: Cocrystals were successfully developed by sonocrystallization method. Sonocrystallization method can be used as a preferred method for formation of drug-drug cocrystals for coadministrative approach of drug delivery.